2006
DOI: 10.1002/cncr.22284
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical utility of p16INK4a immunolocalization with the presence of human papillomavirus by hybrid capture 2 for the detection of cervical dysplasia/neoplasia

Abstract: BACKGROUND. Evidence suggests that overexpression of p16INK4a protein indicates infection and genomic integration of high‐risk human papillomavirus (HR HPV) and predicts progression to cervical high‐grade squamous intraepithelial lesions (HSILs) and carcinoma. The authors compared the ability of p16INK4a and HR HPV detection by Hybrid Capture 2 (HC2) to detect the presence of significant cervical disease. METHODS. Four hundred ThinPrep® specimens (100 each in 4 categories: 100 specimens that were negative for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…Evidence suggests that overexpression of the p16 INK4A protein indicates infection with and genomic integration of high-risk HPV [28]. Despite overexpression of p16, HPV-infected cells continue to proliferate because Rb, the target of p16 inhibitory activity, is inactivated by the E7 HPV oncoprotein [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that overexpression of the p16 INK4A protein indicates infection with and genomic integration of high-risk HPV [28]. Despite overexpression of p16, HPV-infected cells continue to proliferate because Rb, the target of p16 inhibitory activity, is inactivated by the E7 HPV oncoprotein [29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite overexpression of p16, HPV-infected cells continue to proliferate because Rb, the target of p16 inhibitory activity, is inactivated by the E7 HPV oncoprotein [29]. Therefore, p16 has been used as a predictor of cervical high-grade squamous intraepithelial lesions and carcinoma due to HPV-induced cell cycle dysregulation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Two potential explanations for this include an ability to ignore stained basal or focal staining of metaplastic cells on the tissue but not on cytology and/or deficiencies in the ThinPrep methodology used for this study. A study by Holladay et al 15 also expressed concern regarding truly negative cells demonstrating p16 staining.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In the majority of the studies, p16 cytology was found to provide sensitivity rates for the detection of underlying high-grade cervical intraepithelial neoplasia (CIN of grade 2 or higher, CIN2þ), which were similar or slightly lower compared with the sensitivity of testing for the presence of human papillomavirus (HPV) infections. 7,9,10,11 At the same time, specificity of p16 cytology-based testing was found to be substantially higher than the specificity of HPV testing in all studies.…”
mentioning
confidence: 99%